2015
DOI: 10.5152/tjbh.2014.2322
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Knowledge and Behavior of Women Working at a Hospital on Breast Cancer Early Detection Methods, and Investigation of Efficiency of Planned Education

Abstract: Objective: This study aimed to evaluate knowledge and attitude of women working in the hospital on breast cancer, their behaviors related to early diagnostic methods, and to determine the effectiveness of training in order to increase awareness on breast cancer. Materials and Methods:The study group consisted of women working in the Dokuz Eylül University Hospital. The data of this cross-sectional study were collected by a questionnaire. Within the scope of this study, a training program on breast cancer was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 16 publications
2
5
0
3
Order By: Relevance
“…This study found, like previous studies, that female academicians who do BSE have lower perceived barriers [11–14]. Turkish academicians had less perceived barriers and higher self-efficacy levels [13].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This study found, like previous studies, that female academicians who do BSE have lower perceived barriers [11–14]. Turkish academicians had less perceived barriers and higher self-efficacy levels [13].…”
Section: Discussionsupporting
confidence: 87%
“…The percentage of academicians in this study who perform monthly BSE (41.5%) was much higher than the previous Turkish studies conducted with academicians [11–14]. Yılmaz et al (2011) found that female academicians did the recommended BC screening tests such as BSE, CBE and mammography more than housewives [14].…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…It was emphasized in a study that the women having a history of BC in their family had mammography screening 1.98 times (95% CI: 1.20-3.25) more regularly than those not having a history of BC in their family, and the women being detected with a suspicious formation in the mammography had mammography screening 1,47 times 95% CI: 1-2.16) more regularly than those not being detected with a suspicious formation in the mammography [6]. It was also determined in other studies that the women having a history of BC in their family and/or having abnormal mammography findings had mammography screening more regularly [38]. Our findings are compatible with these results.…”
Section: Discussionmentioning
confidence: 87%